The Interaction between Self-Esteem, Perceived Gender Discrimination and Employment Motivation: A Log-Linear Analysis - Durukan, Kübra; Öncel, Sevgi Yurt; Erdugan, Funda (International Journal of Statistics in Medical Research, 2024)
This study analyzes the relationships between self-esteem, perceived gender discrimination, and employment motivation. Results show that individuals not perceiving gender discrimination are 3.66 times more prevalent than those who do. Individuals who see the purpose of employment as a way to improve themselves are 1.8 times more motivated than those who want to contribute meaningfully to society. Self-improvement is a stronger motivator than contributing to society, and income-focused individuals show 2.8 times higher motivation. Those with low self-esteem aspiring to contribute to society are 2.6 times more likely to be motivated than those focusing on self-improvement. Achieving gender equality and preventing discrimination can enhance personal development and societal contributions, leading to increased individual success and social welfare. The motivations of self-development and usefulness to society make the strongest contribution to an individual's self-esteem. These motives are related to inner satisfaction and social recognition.